Endodontic and Prosthetic Management of a Mid-Root and Crown Fracture of a Maxillary Central Incisor - Koidou Vasiliki P.; Lambrianidis Theodoros (Balkan Stomatological Society, 2014)
Root fractures are relatively uncommon among other dental traumas and mostly affect the anterior dentition. This case report presents the endodontic and prosthodontic management of a maxillary central incisor with a combined fracture in the middle third of the root and the crown, as well as the 7-year follow up of the case. The healing potential of a horizontal root fracture in the middle third of the root is highlighted when appropriate treatment is applied. MTA used for obturation of the coronal fragment, induced hard tissue formation apically and promoted healing in the area, while the 2mm MTA left as apical barrier at the second stage of re-treatment and obturation with gutta-percha prevented its extrusion. The multidisciplinary approach in the management of such cases ensures a long term survival.